A national study on the use of opioid analgesics in dentistry - Patrícia Azevedo LINO; Woosung SOHN; Astha SINGHAL; Maria Auxiliadora Parreiras MARTINS; Maria Elisa de Souza e SILVA; Mauro Henrique Nogueira Guimarães de ABREU
Abstract The aim of this study was to assess the frequency of opioid analgesics prescribed by Brazilian dentists, potential regional differences and their association with socioeconomic and health-related factors. Data for all opioid prescriptions by dentists was obtained from the 2012 database of the National Controlled Substances Management System, regulated by the Brazilian Health Surveillance Agency. The number of defined daily doses (DDD) and DDDs per 1,000 inhabitants per day for each Brazilian state were calculated as the primary outcomes. DDDs were compared by regions and Brazilian states. Spearman's rho correlation coefficient was used to determine the influence of the states' characteristics, such as the Human Development Index; poverty; education; number of dentists per 100,000 inhabitants; visit to the dentist; dental care plan; good or very good oral health; number of pharmaceutical establishments per 100,000/inhabitants; and ability to get all prescribed medications. Data analysis was performed using IBM SPSS Statistics 25.0. A total of 141,161 prescriptions for opioids analgesics by 36,929 dentists were recorded, corresponding to 658,855 doses of opioids dispensed in 2012. The most commonly dispensed opioids were codeine associated with paracetamol (83.2%; n = 117,493). The national DDDs per 1,000 inhabitants per day was 0.0093 (range: 0.0002-0.0216). DDD per 1,000 inhabitants per day was positively associated to visits to dentists (rs = 0.630; P < 0.001) and inversely associated to poverty (rs = -0.624; p = 0.001). There are significant differences in opioid prescriptions in dentistry among the Brazilian states. These differences may be associated with non-clinical factors.